Comparative analysis of three bronchopulmonary dysplasia diagnostic criteria in predicting longterm neurodevelopmental outcomes in preterm infants - Rui Li; Xin Wang; Yanyan Wu; Qiqi Bu; Jing Guo; Dapeng Liu; Yingyuan Wang; Xiaoyuan Zhang; Changlian Zhu; Wenqing Kang (Scientific Reports)
Abstract This study compared the predictive value of three diagnostic criteria for bronchopulmonary dysplasia (BPD) in relation to death or neurodevelopmental impairment (NDI) at a corrected age of 24 months in preterm infants born before 32 weeks’ gestation. In this retrospective cohort study conducted at a single center, 508 preterm infants with a median gestational age of 30.0 weeks were admitted between January 2019 and December 2021. BPD was diagnosed using the 2001 NICHD, 2018 NICHD, and 2019 Jensen definitions. Multivariate logistic regression and receiver operating characteristic (ROC) curve analysis were used to assess the predictive value of each definition. Of the infants, 52 (10.2%) experienced death or NDI. Severe BPD defined by the 2018 NICHD and 2019 Jensen criteria, and the presence of periventricular leukomalacia (PVL), were significant risk factors for adverse outcomes. Both the 2018 NICHD and 2019 Jensen definitions demonstrated superior predictive value compared to the 2001 NICHD definition. Combining these criteria with PVL further improved prediction efficiency. These findings suggest that newer BPD definitions, especially when combined with neuroimaging indicators, enhance prognostic accuracy for long-term neurodevelopmental outcomes in preterm infants.